Regulating international business through codes of conduct - Waldmann, Raymond J. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The book examines a relatively new phenomenon - - international code of regulations for multinational enterprises and international business transactions which have become a focal point in the "North-South" dialogue, between the less developed countries and the economically developed world of Europe, North America, and Japan.
Bibliography: p.
gp. 23/01/2019
Loan
Keywords: Trade regulation; International business enterprises; International economic relations; United States